PENGARUH AGENCY COST TERHADAP KINERJA KEUANGAN BUMN DI BIDANG PERTAMBANGAN, INDUSTRI STRATEGIS, ENERGI DAN TELEKOMUNIKASI (PISET) - FUADAH, TSAMROTUL (Jurnal Akuntansi AKUNESA, 2013)
The purpose of this research is to examine the effect of agency cost on firm performance. This research take sample from 10 companies from Mining, Strategic Industry, Energy and Telecomunication (PISET) which were published in financial report from 2009, 2010, 2011 and 2012. The method of analysis of this research used simple linier regression. The result of this research that negative significant effect of agency cost on firm performance. The negative effect was caused by the decrease of others income/(expense) and  Advantage tax (expense). Keyword: agency cost, firm performance, simple linier regression